Toxicity parameters of a new 1,2,4-triazole derivative when subcutaneously injected to guinea pigs - Zazharskyi, V. V.; Bigdan, O. A.; Parchenko, V. V.; Karpenko, Y. V.; Zazharska, N. M.; Mykhailiuk, Ye. O.; Kulishenko, O. M.; Davydenko, P. O.; Kulish, S. M.; Gutyj, B. V.; Бігдан, Олексій Антонович; Парченко, Володимир Володимирович; et al. (My University, 2024)
The results of the literature analysis indicate a wide spectrum of biological activity of 1,2,4-triazole derivatives. Low toxicity, reactivity, and high biological activity of 1,2,4-triazole derivatives make this class of compounds very attractive. The obtained data determine the relevance of further studies of 1,2,4-triazole derivatives to find new highly effective biologically active substances that can become the basis for new medicines. Our further work aimed to study some toxicity parameters of 3-(3-fluorophenyl)-6-(4-methoxyphenyl)-7H-[1,2,4]-triazolo-[3,4-b][1,3,4] thiadiazine when administered subcutaneously to guinea pigs, which is a necessary condition for further implementation in practice of this compound. In this work, we observed an absence of toxic effects after a single subcutaneous injection to guinea pigs at a dose of 40 mg/kg experimental drug. The results of macro- and microscopic examinations of internal organs 14 days after a single subcutaneous injection of the studied compound at a dose of 20, 40 mg/kg showed the absence of any anatomical and morphological disorders in the tissue structures of guinea pigs. The calculated value indicates a high degree of safety of 3-(3-fluorophenyl)-6-(4- methoxyphenyl)-7H-[1,2,4]-triazolo-[3,4-b][1,3,4] thiadiazine and its prospects for use in veterinary practice as an effective and safe tuberculocidal agent.
Keywords: safety; acute toxicity; chronic toxicity; enzymes; biochemical parameters